PERUBAHAN IKLIM DALAM PENGELOLAAN EKOSISTEM MANGROVE MELALUI PENDEKATAN EKOLOGI, EKONOMI DAN SOSIAL BUDAYA MASYARAKAT DI TELUK KOTANIA - Hellen Nanlohy; Ambaryanto Ambaryanto; Azis Nur Bambang; Sahala Hutabarat (PAPALELE: Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan, 2017)
Climate change is powerful on the growth of mangrove.The adaptation to climate change is an urgent need to minimize the impact of climate change.This study attempts to assess the impact of climate change on mangrove growth and formulating a program community adaptation to climate change the ecological, economic indicators, social and cultural community. The analysis survey was conducted qualitatively and analysis image Data Lansat ETM 8. The analysis shows climate change influenced the growth mangrove. The community adaptation to be applied is giving the use of a catch environmentally friendly, diversification of fruit trees. Other alternative business the fish and seaweed and participation in supporting the government programs.The adaptation others are cooperation between the government and the community in an effort to reforestation and rehabilitision. Tradition sasi mangrove came to watch to preserve the ecosystem mangrove.